2012
DOI: 10.1128/jvi.00019-12
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-Wide Overexpression of Host Proteins for Identification of Factors Affecting Tombusvirus RNA Replication: an Inhibitory Role of Protein Kinase C

Abstract: To identify host genes affecting replication of Tomato bushy stunt virus (TBSV), a small model positive-stranded RNA virus, we overexpressed 5,500 yeast proteins individually in Saccharomyces cerevisiae , which supports TBSV replication. In total, we identified 141 host proteins, and overexpression of 40 of those increased and the remainder decreased the accumulation of a TBSV replicon RNA. Interestingly, 36 yeast proteins were identified previously by various sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 90 publications
0
28
0
Order By: Relevance
“…The host proteins interacted with the viral replication proteins and viral RNA or affected TBSV replication and recombination when deleted/downregulated or overexpressed in host cells (11,13,(40)(41)(42)(43)(44)(45)(46)(47)(48). Cataloging of the host factors affecting TBSV replication is one of the most complete among pathogens at a single cell level, thus facilitating mechanistic studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The host proteins interacted with the viral replication proteins and viral RNA or affected TBSV replication and recombination when deleted/downregulated or overexpressed in host cells (11,13,(40)(41)(42)(43)(44)(45)(46)(47)(48). Cataloging of the host factors affecting TBSV replication is one of the most complete among pathogens at a single cell level, thus facilitating mechanistic studies.…”
mentioning
confidence: 99%
“…The yeast Nedd4-type Rsp5p E3 ubiquitin ligase carrying WW domain was identified in several genome-wide screens previously (13,42,48). In addition to Rsp5p, several cellular WWdomain proteins, including Wwm1p, Prp40p, and plant AtDrh1, AtFCA, and AtPrp40c, bind to the tombusvirus replication proteins and inhibit their functions (64,65).…”
mentioning
confidence: 99%
“…Another group of cellular restriction factors is the WW motif-containing host proteins, such as Rsp5p Nedd4-like E3 ubiquitin ligase, which regulate the degradation of tombusviral p92 pol in yeast cells and inhibit the activity of VRC in vitro (45,46). Cellular kinases, such as Pkc1p, could also restrict TBSV replication in yeast (32). Taken altogether, studies of cellular restriction factors could help to unravel the full arsenal of the native cellintrinsic innate immune system in the host cell.…”
mentioning
confidence: 99%
“…We have performed several genome-wide screens of yeast genes by using different global proteomics approaches that have led to the identification of over 500 host genes/proteins putatively involved in TBSV replication or recombination (17,19,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The abovementioned systematic screens have identified host stimulatory and restriction factors of TBSV replication.…”
mentioning
confidence: 99%
“…ecent genome-wide screens have revealed that replication of RNA viruses inside the infected cells depends on hundreds of factors, most of which have not been characterized (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). In addition, RNA viruses extensively rewire the cells by changing metabolic, secretory, and trafficking pathways, reorganize host membranes, and alter quality control mechanisms (17,18).…”
mentioning
confidence: 99%